Virtual and Augmented Reality and People Selection: a systematic analysis review. - Figueiredo, Clara; Carneiro, Andreia; Torres, Manuela; Valente, Maria; Santos, Mariana; Silva, Mariana; Seixas, Daniela; Costa, Daniel; Correia, Tiago; Lopes, Liliana; Meirinhos, Viviana; Rodrigues, Ana Cláudia; et al. (Conferência - Investigação e Intervenção em Recursos Humanos, 2019)
In our daily routine we have some APP to help us in some activities that in the past people used to resolve them manually. Organizations are increasing its presence in a digital world too with more people working in virtual workplaces everywhere, so it is urge to improve some changes in the actual paradigm of the work environment and introduce the Virtual Reality as a tool to increase results and decrease precious time used to produce more. Virtual Reality and Augmented Reality applied at the Human Resources processes should help to create a virtual environment to replicate the company activity in order to achieve this goal. With this revision the author pretends to map all papers about Virtual Reality and Augmented Reality in Human Resources for People Selection in order to identify the main possibilities of this tool to improve and develop new products and more accurate studies for the Human Resources Management.